Multi-objective Orthogonal Test Simulation and Modification Parameter Design based on Ease-off Topology - Jiaqi Li; Congcong Song; Bingyang Wei (Jixie chuandong)
To improve the comprehensive dynamic meshing performance of a certain gear product， a design method for controlling the polynomial coefficients of the topological modification of the tooth surface is proposed. By using Ease-off surface， through the loaded tooth contact analysis and elastohydrodynamic lubrication model， the gear transmission error and meshing power loss are calculated. Taking the loaded transmission error amplitude， meshing efficiency and its fluctuation as the goals， through orthogonal test design and multi-factors and multi-levels simulation， the best topological modification parameters of the tooth surface are obtained. The influence of modification parameters on meshing performance is analyzed. The results show that the tooth profile is closely related to the spiral profile modification， with the increase of the tooth profile modification ratio， the contact path inclination becomes larger， the load is concentrated in the middle of the tooth surface， the contact ratio of tooth surface and the curvature of contact line difference become larger， which is beneficial to reduce the contact stress of tooth surface， alleviate the edge contact， and reduce the tooth surface friction loss at the same time.